Feedback control strategies for a continuous industrial fluidized-bed granulation process - Cotabarren, Ivana María (2015)
This paper focuses on enhancing the operation of industrial granulation circuits via the design and performance evaluation of different control strategies. Particularly, the control strategies were implemented on a urea flowsheet simulator based on the Uhde fluidized-bed granulation technology (UFT), previously developed in the gPROMS modeling environment (Process System Enterprise) and validated against experimental data by our research group. First of all, an effective strategy for variables pairing in MIMO systems through Relative Gain Array analysis was tested. Continuing with the control system design, the controller parameter tuning was performed coupling an integral of time absolute error method with an optimization strategy. Afterward, the ability of simple feedback controllers (PI) to reject operational disturbances and track desired set-points was analyzed. Advanced techniques such as cascade control were also implemented to improve controller performance. All the studied control loops were effective to either eliminate disturbances in the granulation circuit variables or to reach new set-points for the controlled variables, although it is demonstrated that the cascade configuration outperforms the simple feedback control strategy. Summarizing, this contribution provides granulation process engineers with useful control strategies for solving typical transient operational challenges.